Trench Bending Initiation: Upper Plate Strain Pattern and Volcanism. Insights From the Lesser Antilles Arc, St. Barthelemy Island, French West Indies. Issue 9 (4th September 2018) - Legendre, L.; Philippon, M.; Münch, Ph.; Leticée, J. L.; Noury, M.; Maincent, G.; Cornée, J. J.; Caravati, A.; Lebrun, J. F.; Mazabraud, Y.
Abstract: The upper plate deformation pattern reflects the mechanical behavior of subduction zones. Here we focus on the consequences of the entrance of a buoyant bank into the Caribbean subduction zone during the Eocene by studying the oldest exposed rocks belonging to the Lesser Antilles volcanic arc. Using a novel geochronological data set, we show that the volcanic arc activity on the island of St. Barthelemy spanned over the mid‐Eocene to early Miocene with a westward migration of the tectono‐volcanic activity, which is comparable to what has already been observed on other volcanic islands in the Lesser Antilles. The kinematics analysis allows us to identify a switch in the stress field from pure to radial extension at the Oligo‐Miocene hinge with a subhorizontal σ3 that has a mean trend of N20°. A three‐step restoration of the regional deformation indicates that this switch from pure parallel‐to‐the‐trench extension to radial extension may reflect a strain partitioning initiation affecting the upper Caribbean Plate in response to trench bending that followed the entrance of the Bahamas Bank into the subduction zone. We show that the northern end of the Lesser Antilles arc shows a tectono‐volcanic evolution which is similar to the southern one. The north‐south dichotomy in the perpendicular‐to‐the‐trench extension, 15% in the north versus 30% in the south, may reflect different slab ends that are highly curved to the north (restraining the extension in the upper plate) versus a tear to the south (allowing a larger amount of extension within the upper plate). Key Points: The extinct Lesser Antilles arc shows a westward migration of the tectono‐magmatic activity during the middle Eocene‐Miocene period Paleostress inversions reveal that the stress regime evolved from pure to radial extension over the Eocene‐Lower Miocene time span This switch in the upper plate strain pattern accommodates the bending of the trench that followed the Bahamas Bank collision